Pursuit of fairness in household financial arrangements among young middle-class couples in Poland. (May 2020) - Olcoń-Kubicka, Marta
Drawing on ethnographic research into household money practices among young middle-class couples in Warsaw, Poland, this article shows that normative concerns about the fair use of domestic money shape household budgeting rules. The practical division of funds into 'mine', 'yours' and 'ours' reflects what couples running a household together consider morally right. Focusing on couples' practical and moral reasoning, I show the set of expectations and the moral logic they employ to achieve fairness in their household financial arrangements. The analysis of two models of domestic money allocation – the 50–50 model, which is based on a couple's equal contributions, and the joint-money model, which involves a couple's recognition of mutual obligations – highlights how fairness is articulated in rules about equality, independence and solidarity. By studying couples through time as they experience significant life changes, I show how the rules of fairness come to be challenged and how what is considered fair is questioned or even contested. I argue that turning points such as taking out a mortgage together or having a child produce new expectations and imaginaries about the future and prompt couples to question the rules of fairness and consequently to change their money practices.